Agreement between different pathologists in histopathologic diagnosis of 128 gastric polyps - Barbosa, Sérgio Henrique Brito (2017)
BACKGROUND - Gastric polyps are elevated mucosal lesions. Most of them are less than 1 cm and when larger than 2 cm, has a high malignancy probability. The histopathological types are mainly fundic gland polyps, hyperplastic polyps and adenomatous polyps. OBJECTIVE - To evaluate the agreement between three different pathologists in the histopathological diagnosis of 128 biopsied gastric polyps in Digestive Endoscopy Unit from Walter Cantídeo University Hospital, between May 2010 to May 2012. METHODS - To describe the intensity of agreement between observers, we use kappa index that is based on the number of concordant measures between them. RESULTS - There was substantial agreement in the diagnosis of adenoma (kappa=0.799, CI: 0.899-0.698) and fundic glands (kappa=0.655, CI: 0.755-0.555). Regarding to hyperplastic polyps (kappa=0.415, CI: 0.515-0.315) and inflammatory (kappa=0.401, CI: 0.501-0.301), we obtained a moderate agreement. Regarding the presence of Helicobacter pylori in biopsy of the polyp, there was a low agreement (kappa=0.219, CI: 0.319-0.119). CONCLUSION - It is clear that the agreement between pathologists depends on the histological type of the biopsied polyp and this agreement is more substantial in adenoma, or fundic gland polyps.